Safe havens and evacuation routes due to dam disaster - Mamat, Ahmad Fadhli; Mohd. Hussain, Mohd. Ramzi; Tukiman, Izawati; Sabri Muda, Rahsidi; Rabe, Noor Suzilawati (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2019)
The aim of the paper is to review the important framework and understanding for the safe havens and evacuation routes due to dam disaster.There is estimated amount of 33,000 dams around the world today in the category of large dams. From the year of 1800, there are about 300 major dam failure occurred, causing thousands of casualties. Although dam owners have taken all the possible precautions, the possibility of incidents to occur remains there due to controlled and uncontrolled situations. In Malaysia, there are more than 20 large dams available, built for different purpose ranging from hydro power generation, water supply, crop irrigation and also for flood mitigation. The first large dam constructed in Malaysia is Bukit Merah Dam in Kerian, Perak in the year of 1906 and the construction continues until the most recent dam, Susu Dam in Jelai, Pahang, completed in the year of 2016. TNB being the dam owner of large dams for hydro power generation in Malaysia for example, has 14 large dams with the largest being the Kenyir Dam in Terengganu, having the capacity of 13,600 million cubic meters of water and dam high of 150 meters. The paper reviews the aspect of safe havens and evacuation routes in order to secure the surrounding communities. It also covers on how the community evacuate safely from the disaster. Based on this framework, it is hoped that the paper will be a useful addition to the body of knowledge and understanding for the safe havens and evacuation routes and also a safety and awareness community during the disaster.